Entre poesía e historia: La materia ovidiana en la obra alfonsí - Salvo García, Irene (Troianalexandrina, 2014)
Abstract In this article, starting from a thorough study of the translation of Ovid’s Metamorphoses in the General Estoria undertaken in our Ph.D., we establish the guidelines that characterise this reception, and more specifically the compilers’ work and their position with respect to the historic use of a literary work. We prove that King Alphonse X’s desires about his historiographical project are not always compatible with the constraints his collaborators meet. The Alphonsines receive clear instructions from the king himself: they do their best to rationalise them in order to build a historic narrative out of diverse and contradictory sources such as Biblical, historic and mythological texts. Thus, the compilation criteria applied to the pagan matter logically vary depending on the difficulty to include supernatural elements - e.g., physical transformations of a deity into an animal - the explanations of which can be found only in the margins of the Latin manuscript. How to authorise a scattered, scholarly and anonymous matter like the glosses to include it in the canonical sources of history? Thanks to the analyses of its literary and pagan sources, we observe, to conclude, that the General Estoria is eclectic and sometimes paradoxical. This feature reflects the difficulty to establish an exhaustive narration of the history of the world that takes into account all religious confessions and keeps a unity at the same time.